The + 3010/C single nucleotide polymorphism (rs1710) at the HLA-G 3′ untranslated region is associated with a short transcript exhibiting a deletion of 92 nucleotides - Castelli, Erick C. [UNESP]; Paes, Gabriela Sato [UNESP]; da Silva, Isabelle Mira [UNESP]; Moreau, Philippe; Donadi, Eduardo A. (Springer Nature, 2023)
The physiological expression of HLA-G is mainly observed in the placenta, playing an essential role in maternal–fetal tolerance. Among the HLA-G mRNA alternative transcripts, the one lacking 92 bases at the HLA-G 3′ untranslated region (3′UTR), the 92bDel transcript, is more stable, is associated with increased HLA-G soluble levels, and was observed in individuals presenting a 14 bp insertion (14 bp+) at the 3′UTR. We investigated the presence of the 92bDel transcript in placenta samples, correlating its expression levels with the HLA-G polymorphisms at the 3′UTR. The 14 bp+ allele correlates with the presence of the 92bDel transcript. However, the polymorphism triggering this alternative splicing is the + 3010/C allele (rs1710, allele C). Most 14 bp+ haplotypes (UTR-2/-5/-7) present allele + 3010/C. However, 14 bp− haplotypes such as UTR-3 are also associated with + 3010/C, and the 92bDel transcript can be detected in homozygous samples for the 14 bp- allele carrying at least one copy of UTR-3. The UTR-3 haplotype is associated with alleles G*01:04 and the HLA-G lineage HG0104, which is a high-expressing lineage. The only HLA-G lineage that is not likely to produce this transcript is HG010101, associated with the + 3010/G allele. This functional difference may be advantageous, considering the high worldwide frequency of the HG010101 lineage. Therefore, HLA-G lineages are functionally distinct regarding the 92bDel transcript expression, and the 3010/C allele triggers the alternative splicing that produces this shorter and more stable transcript.
Keywords: 3′UTR; 92 base deletion; Alternative splicing; Alternative transcript; Expression; HLA-G; Polymorphism